X-ray excited optical luminescence at Carnaúba, the Sirius X-ray nanoprobe beamline - Verônica C. Teixeira; Joelson C. Silva; Francisco C.M. Silva; Rodrigo Szostak; Maria Gabriella D. Guaita; Leonardo M. Kofukuda; Antonio C. Piccino Neto; Anna P.S. Sotero; Itamar T. Neckel; Carlos A. Pérez; Douglas Galante; Hélio C.N. Tolentino (Optical Materials: X, 2023)
This work presents the developments and initial results obtained using X-ray excited optical luminescence (XEOL) at the Carnaúba, the nanoprobe beamline from Sirius, the Brazilian 4th generation synchrotron source. XEOL is a highly important tool to study luminescence mechanisms and identify optical channels in various types of materials under X-ray irradiation. Using this capability combined with a nanoprobe, one can probe optical channels, for example, in heterogenous materials, and directly correlate them with chemical composition, oxidizing state of absorbers, structure and/or morphology in simultaneous studies. Carnaúba is composed by two experimental station and at the Tarumã station, the first entering in operation, it has been possible to investigate XEOL in the integrated and emission modes, and 2D images in hyperspectral mapping with submicrometric resolution. Herein, it is showed some examples of studies combining excitation energy, emission wavelength and emission intensity in 3D spectra, 2D imaging, and XEOL emission on the study of very sensitive samples that can be easily damaged by the probe. This work also highlights some of the upcoming developments that include the time-resolved and in situ experiments, this last one using microfluidic cells, and the improvement of the covered emission wavelength up to 1700 nm, which will open new opportunities for studying optical materials.